Pengaruh Manfaat, Kemudahan, dan Pendapatan terhadap Minat Menggunakan Paylater : Studi Kasus Masyarakat DKI Jakarta - Sawitri , Yulia; Fathihani, Fathihani (Siber Nusantara Publisher, 2023)
This study aims to examine the effect of perceived usefulness, perceived ease of use and income on interest of using paylater services. The population in this study is the people of DKI Jakarta who know the Shopee Paylater service. The research method used is quantitative method with primary data obtained from distributing questionnaires with a total sample of 144 people domiciled in DKI Jakarta. The analytical method uses the Partial Least Square Structural Positive and Equation Model (SEM) application (smartPLS 4.0). Perceived usefulness, perceived ease of use and income have a positive and significant effect on intention to use; The novelty of the research is taking the object of research, namely paylater services.